2013
DOI: 10.1016/j.dnarep.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma pigmentosum complementation group C protein (XPC) serves as a general sensor of damaged DNA

Abstract: The xeroderma pigmentosum complementation group C protein (XPC) serves as the primary initiating factor in the global genome nucleotide excision repair pathway (GG-NER). Recent reports suggest XPC also stimulates repair of oxidative lesions by base excision repair. However, whether XPC distinguishes among various types of DNA lesions remains unclear. Although the DNA binding properties of XPC have been studied by several groups, there is a lack of consensus over whether XPC discriminates between DNA damaged by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…For example, CPD are recognized and repaired even after DDB2 is degraded (12) or when the number of lesion sites exceeds the number of DDB2 molecules in the cell (13). In addition, XPC recognizes and starts NER at other types of DNA damages, such as bulky adducts and cross-links that are not likely to be recognized by DDB2, because these lesions cannot be accommodated in DDB2′s recognition pocket (14)(15)(16).…”
Section: Significancementioning
confidence: 99%
“…For example, CPD are recognized and repaired even after DDB2 is degraded (12) or when the number of lesion sites exceeds the number of DDB2 molecules in the cell (13). In addition, XPC recognizes and starts NER at other types of DNA damages, such as bulky adducts and cross-links that are not likely to be recognized by DDB2, because these lesions cannot be accommodated in DDB2′s recognition pocket (14)(15)(16).…”
Section: Significancementioning
confidence: 99%
“…Interestingly, the XPC complex appears to recognize lesion-containing secondary DNA structures rather than lesions themselves (7). The nature of the lesion has little effect on the binding affinity of the XPC complex (8). For instance, the XPC complex is equally capable of binding to DNA substrates that are not repaired in vivo by NER, suggesting that XPC may be a general sensor of DNA lesions.…”
mentioning
confidence: 99%
“…Studies have shown that XPC preferentially binds to damaged DNA, yet the type of the lesion does not affect binding efficiencies [12, 13]. Furthermore, these studies demonstrated that XPC binds to lesions that are not even repaired by GG-NER [13].…”
Section: First Contact: Rad4/xpc Binding Specificitymentioning
confidence: 99%
“…Furthermore, these studies demonstrated that XPC binds to lesions that are not even repaired by GG-NER [13]. Appropriately considering XPC and Rad4 share most homology at their DNA binding domains, these two damage sensors bind DNA in the same topological manner [9, 14].…”
Section: First Contact: Rad4/xpc Binding Specificitymentioning
confidence: 99%
See 1 more Smart Citation